Effect of the entomopathogenic fungus Isaria fumosorosea on physiological processes in insects - Gautam, Umesh Kumar (Jihočeská univerzita, 2020)
The project is focused on a study of the infection elicited by entomopathogenic fungus (EPF) Isaria fumosorosea in two model species - the firebug Pyrrhocoris apterus and cockroach Periplaneta americana - and a role of adipokinetic hormones (AKHs) during that. The AKHs are neuropeptides that belong to the AKH/RPCH family and are known mainly for the mobilisation of energy reserves. The AKH role during the fungal infection was monitored by determination of mortality, gene expression in CNS, level of anti-oxidative stress markers, general metabolism, level of nutrients and activity of digestive enzymes. The I. fumosorosea infection elicited severe stress in the infected insects as documented by increase of the AKH expression and AKH levels in CNS of both insect models. The mortality test showed that application of AKH increased the efficacy of EPF application. It is supposed that AKH stimulated higher turnover of fungal toxins by enhanced intensity of metabolism (documented by higher carbon dioxide production) and encouraged the fungus growth by enrichment of haemolymph (a medium for the fungus) by mobilised nutrients. Interestingly, I. fumosorosea affected also digestive processes with substantial inhibition in midgut and partial inhibition in the caeca of male cockroach's digestive enzymes. Another part of this work was to examine changes of the vitellogenin (Vg) level in P. apterus after the I. fumosorosea treatment. The infection significantly reduced the Vg transcript level (checked by quantitative real-time PCR) in the female fat body and protein level in haemolymph (checked polyacrylamide gel electrophoresis). Interestingly, in the male fat body, Vg transcript level significantly increased after the infection, but EPF did not change protein level of male hemolymph. The obtained results point to an interesting role of Vg in insect defence reactions against EPF and are a good example of a trade-off between the Vg function in reproduction and defence reaction. Results of the project might be useful for better understanding of the mechanism of action of entomopathogenic fungi versus AKH, and could be utilised for practical biocontrol of the insect pests in future.
Effect of the entomopathogenic fungus Isaria fumosorosea on physiological processes in insects
Effect of the entomopathogenic fungus Isaria fumosorosea on physiological processes in insects
Keywords: entomopathogenic fungus; Isaria fumosorosea; Pyrrhocoris apterus; Periplaneta americana; adipokinetic hormones; oxidative stress; vitellogenin and insect pests; entomopathogenic fungus; Isaria fumosorosea; Pyrrhocoris apterus; Periplaneta americana; adipokinetic hormones; oxidative stress; vitellogenin and insect pests